BUDISMO EM THICH NHAT HANH E EM CHÖGYAM TRUNGPA RINPOCHE NO PENSAMENTO DA EDUCAÇÃO LIBERTÁRIA DE BELL HOOKS = EL BUDISMO EN THICH NHAT HANH Y EN CHÖGYAM TRUNGPA RINPOCHE EN EL PENSAMIENTO DE LA EDUCACIÓN LIBERTARIA DE BELL HOOKS = BUDDHISM IN THICH NHAT HANH AND IN CHÖGYAM TRUNGPA RINPOCHE IN THE THOUGHT OF LIBERTARIAN EDUCATION BY BELL HOOKS - Lemos, Flávia Cristina Silveira (Estudos de religião, 2025)
This article aims to highlight some points of intersection between bell hooks' libertarian education thinking, her Black feminism, and critique of sexism, racism, military imperialism, and dogmatic religiosity, through its relationship with the Buddhism of Thich Nhat Hanh and Chögyam Trungpa Rinponche. Both Hanh's activist and pacifist Zen Buddhism and Tibetan Buddhism, which critiques the self and alienation associated with magic and sexual liberation, brought relevant analytical dimensions of a critical attitude toward the present, through mindfulness and the hope of a process of community teaching associated with transgressive education and positioned against racism, sexism, domination, sexual and gender oppression, as well as a strong critique of weaponry and self-centered religiosity. Thinking with the concomitance of action without losing sight of the common, seeking a critical embrace, was a significant contribution of Buddhism to bell hooks's Black feminist thought, a process of self-care and urban care.